From Extraordinary to Ordinary: Heroic Images in British and Chinese 18th-century Supernatural Fiction - Minglun Chen; Malini Ganapathy; Salasiah Che Lah (SAGE Open)
Heroic images appear in ancient myths, legends, or folktales from almost every corner of the world. The Swiss psychologist Carl Jung proposed the concepts of the collective unconscious and archetypes in the early 20 th century, and his hero archetype has inspired numerous literary critics, mythologists, and writers to investigate the narrative structures of the hero’s journey. The 18 th century witnessed a boom in British Gothic novels and Chinese supernatural tales, among which Horace Walpole’s The Castle of Otranto and Pu Songling’s Liaozhai Zhiyi are the most prominent. Both literary genres belong to supernatural fiction, with the hero being the typical character. Based on archetypal criticism and qualitative approaches like comparative method, historical approach, and textual analysis, this study attempts to compare the heroic images in British and Chinese 18 th -century supernatural fiction, revealing the resemblance and diversity of human cultures through the analysis of the heroes’ characteristics and journeys in The Castle of Otranto and Liaozhai Zhiyi . The findings show that their heroic images are created by the hero archetypes from their national mythologies and social contexts, which demonstrates the transformation from the extraordinary to the ordinary.